The Iron Cage Revisited: Institutional Isomorphism and Collective Rationality in Organizational Fields (translated by G. Yudin) - Paul Di Maggio; Walter W. Powell (Journal of Economic Sociology, 2010)
What makes organizations so similar? We argue that the engine of bureaucratization and rationalization has moved from the competitive marketplace to the state and the professions. Once a set of organizations emerges as a ﬁ eld, an unusual paradox arises: trying to change them actors make organizations similar. We describe three isomorphic processes — coercive, mimetic, normative — contributing to this outcome. Then we formulate hypotheses about the impact of resource centralization and dependency, goal ambiguity and technical uncertainty, and professionalization and structuration on isomorphic change. Finally we suggest some implications for theories of organizations and social change.